Pelatihan Kader Kesehatan Sekolah untuk Meningkatkan Pelaksanaan Protokol Kesehatan di Sekolah Dasar Kota Padang - Rika Sabri; Mulyanti Roberto Muliantino; Meri Neherta; Dewi Eka Putri (Warta Pengabdian Andalas, 2021)
The increase in Covid-19 cases has opened a new cluster of schoolchildren. Most cases are found in school-aged children, elementary. The state of the pandemic has prevented health workers from carrying out their duties to provide health education about preventing Covid-19 cases in schools. This community service aims to form health cadres in schools who invite school communities to carry out health protocols and live healthy lives to avoid the transmission of Covid-19. Peer learning is a quick way to change behaviour in schools. The community engagement method was to provide training to children in terms of knowledge and skills about Covid-19, its effects, and prevention efforts through washing hands, wearing masks, and keeping a distance. The activity was carried out at SD Citra Almadina and SDN 06 Pasar Ambacang, Padang. The material was given alternately by lecturers and students for two days through lecture methods, demonstrations from resource persons and students, and group exercises to do psychosocial therapy, "finger therapy," to avoid stress from online teaching. The training resulted in 10 health cadres for school children, and certificates were given. Knowledge of school health cadres increased by an average of 12 points. The training and legalization that schools provide to children increase their motivation to remind the school community to always maintain health protocols by washing hands with soap, using face masks, keeping their distance, eating healthy food, and vaccinating.